Expert method for differentiation of chub mackerel (Scomber japonicus) and blue mackerel (S. australasicus) in catches - Pavel G. Milovankin; Aleksey A. Somov (Известия ТИНРО)
Only one diagnostic sign is enough for differentiation of chub mackerel Scomber japonicus and blue mackerel S. australasicus working with mass material. It is a number of spines in dorsal fin: chub mackerel has 9-10 (often 9) and blue mackerel has 11-12 spines. Species identification may be done by relative distance between the spines: it is larger by half for chub mackerel. The species differ well by coloration of dorsal side: blue mackerel has «marbled» pattern with thin lines, in contrast to chub mackerel that has «zebra» pattern with thick lines.